2017
DOI: 10.1002/smll.201604048
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Microgels Containing Agglomerates of Silver Nanocubes for Molecular Size‐Selectivity and High SERS Activity

Abstract: Surface-enhanced Raman scattering (SERS) is a promising technique for molecular analysis as the molecular fingerprints (Raman spectra) are amplified to detectable levels compared with common spectroscopy. Metal nanostructures localize electromagnetic field on their surfaces, which can lead to dramatic increase of Raman intensity of molecules adsorbed. However, the metal surfaces are prone to contamination, thereby requiring pretreatment of samples to remove adhesive molecules. To avoid the pretreatment and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…12, the bacteria were captured by the antibodies immobilized in the microchannel with an Au-coated SPR chip, resulting in a local refractive index change due to the binding event. Applications of microfluidics for other plasmonic detections, such as LSPR [172], SERS [173][174][175][176], and SEF [177] have also been extensively studied. For example, Quidant et al reported a parallel LSPR-based immunoassay chip for the real-time detection of AFP and PSA down to concentrations of 500 pg/mL in 50% human serum [172].…”
Section: Plasmonic Microfluidic Devicesmentioning
confidence: 99%
“…12, the bacteria were captured by the antibodies immobilized in the microchannel with an Au-coated SPR chip, resulting in a local refractive index change due to the binding event. Applications of microfluidics for other plasmonic detections, such as LSPR [172], SERS [173][174][175][176], and SEF [177] have also been extensively studied. For example, Quidant et al reported a parallel LSPR-based immunoassay chip for the real-time detection of AFP and PSA down to concentrations of 500 pg/mL in 50% human serum [172].…”
Section: Plasmonic Microfluidic Devicesmentioning
confidence: 99%
“…However, the liposomes and hydrogel‐shelled nanoparticles are difficult to separate and concentrate in practical uses due to small size and a lack of nanogaps provides limited sensitivity. To overcome the limitations of the nanocapsules, nanoparticles or their agglomerates are loaded in microgels using a microfluidic strategy . As the microgels with limiting mesh size allow the infusion of small molecules while excluding large protein, small molecules can be directly detected without pretreatment of the complex biological samples, such as blood; the mesh size is controllable by adjusting molecular weight of monomers .…”
Section: Introductionmentioning
confidence: 99%
“…Kim's group [19][20][21] fabricated a series of SERS-active microgels through coflow-focusing microdroplet generation technique. Through agglomeration [19,20] or droplet shrinking [21], AuNPs can be concentrated in the microgel fabrication process to achieve higher SERS signal. On the other hand, AuNPs inside microgels can be protected from contamination by sample matrix in biologic application.…”
Section: Microfluidic Particle Synthesis Approachesmentioning
confidence: 99%